Chapter 6 Double agent? Ethical considerations in conducting ethnography as a teacher-researcher - Nikkanen, Hanna M. (Taylor & Francis, 2019)
This chapter will focus on the positionality of a teacher-researcher as a moral agent (Macfarlane 2009) when conducting ethnography. As Guillemin and Gillam above, I find the double role of a teacher-researcher informing all the phases of the research. Therefore, reflection is also needed, not only as the final phase of the research project, but throughout the process. I will discuss ethical considerations concerning both the students and the colleagues, moments of reflection and my solutions on how to define the topics and design the methods when conducting ethnography in my own educational community.